Rekayasa Surat Pertanggungjawaban dan Penyalahgunaan Anggaran di DP3APM Kota Tanjungpinang Saat Defisit Anggaran - Al-Zachra Aprilya Jasmon (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
This study investigates allegations of fabricated Accountability Letters (SPJ) and budget irregularities at the Tanjungpinang City Women's Empowerment, Child Protection, and Community Empowerment Agency (DP3APM), just as the regional budget deficit reached Rp97 billion. Internal reports and local media coverage reveal strong indications that funds allocated for outbound activities were diverted to purchase clothing and shoes, which were then used for the Proclamation Walk even though the outbound activities themselves never materialized, raising suspicions of fictitious SPJs and a lack of transparency in the management of public funds. Qualitative descriptive methods were applied through in-depth analysis of news documents, official statements, and regional financial management regulations such as Law No. 23/2014 concerning Regional Government. The analysis highlights violations of fiscal accountability principles under the pressure of the local budget crisis, recommending a comprehensive independent audit by the Supreme Audit Agency (BPK) or regional inspectorates, along with oversight reforms involving the digitization of financial reports to prevent a repeat in other regional governments across Indonesia.